Effects of starvation on serum levels of calcium, phosphorus, uric acid and creatinine in newly hatched broiler chicks - AL-RAWASHDEH, O F; LAFI, S Q; ABDUL-AZIZ, T A; HAILAT, N Q; EREIFEJ, K I (The Indian Journal of Animal Sciences, 2013)
Newly hatched broiler chicks were starved for 1-5 days and their serum levels of calcium, phosphorus, uric acid and creatinine, and body weight, were assessed and compared te their counterparts in fed chicks. A slight and steady decrease in the mean calcium level and a significant decrease (P